2022
DOI: 10.14336/ad.2021.0720
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Metabolite Profile Alterations in the Hippocampus and Cortex of Male and Female Mice Exposed to a Fat and Sugar-Rich Diet are Normalized by Diet Reversal

Abstract: Diabetes impacts on brain metabolism, structure, and function. Alterations in brain metabolism have been observed in obesity and diabetes models induced by exposure to diets rich in saturated fat and/or sugar and have been linked to memory impairment. However, it remains to be determined whether brain dysfunction induced by obesogenic diets results from permanent brain alterations. We tested the hypothesis that an obesogenic diet (high-fat and high-sucrose diet; HFHSD) causes reversible changes in hippocampus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 53 publications
2
47
1
Order By: Relevance
“…Namely, mice fed a lard-based 60%-fat-rich diet for 6 months showed increased taurine in the cortex (+7%), hypothalamus (+9%), and, most prominently, hippocampus (+12%), when compared to low-fat-fed mice [ 159 ]. Recently, we further demonstrated that a high-fat and high-sugar diet led to increased hippocampal levels of taurine after 4 weeks, which persisted for several months (ranging from +8% to +14% relative to low-fat-diet-fed controls), which were reversed by diet normalization [ 38 ]. Such increase in brain taurine levels in mice with diabetes might have resulted from a compensatory mechanism for cellular protection against metabolic syndrome.…”
Section: Brain Taurine In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, mice fed a lard-based 60%-fat-rich diet for 6 months showed increased taurine in the cortex (+7%), hypothalamus (+9%), and, most prominently, hippocampus (+12%), when compared to low-fat-fed mice [ 159 ]. Recently, we further demonstrated that a high-fat and high-sugar diet led to increased hippocampal levels of taurine after 4 weeks, which persisted for several months (ranging from +8% to +14% relative to low-fat-diet-fed controls), which were reversed by diet normalization [ 38 ]. Such increase in brain taurine levels in mice with diabetes might have resulted from a compensatory mechanism for cellular protection against metabolic syndrome.…”
Section: Brain Taurine In Diabetesmentioning
confidence: 99%
“… Concentrations of taurine in the plasma ( A ) and cerebral cortex of various species ( B ), in different areas of the mouse brain ( C ), and in the mouse cortex during development ( D ). Plasma taurine levels are indicated as mean and range for humans [ 2 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], guinea pigs [ 28 , 29 ], rat [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], and mice [ 37 , 38 , 39 , 40 , 41 ]. The plotted brain taurine concentration ranges are based on the concentrations reported in 1 H MRS studies for humans [ 42 , 43 , 44 , 45 , 46 , 47 ], tree shrews [ 48 ], guinea pigs [ 49 ], Sprague–Dawley rats [ 50 , 51 , 52 , 53 , 54 , 55 ], and C57BL/6J mice [ 38 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Figurementioning
confidence: 99%
“…Food and water were provided ad libitum . Diets were acquired from Research Diets (New Brunswick, NJ-USA): a lard-based diet with 60% kcal of fat (D12492) and a control diet containing 10% kcal of fat (D12450J), with total energy of 5.21 and 3.82 kcal/g, respectively, and caloric intake was monitored as previously (García-Serrano et al , 2022).…”
Section: Materials Al Methodsmentioning
confidence: 99%
“…RNA was isolated from the hippocampus with Trizol (#15596026, Invitrogen), and then 1 μg of total RNA was reverse transcribed with random hexamer primers using the qScript cDNA SuperMix (#95048, Quantabio, England), according to the manufacturers’ instructions. The resulting cDNA was used for quantitative RT-PCR as detailed previously (Garcia-Serrano et al ., 2022) using PerfeCTa SYBRgreen SuperMix (#95054, Quantabio, England) and the primers listed in table 1 . Gene expression was determined using the comparative cycle threshold (CT) method (ΔΔCT) with normalization to the average expression of L14 and GAPDH.…”
Section: Materials Al Methodsmentioning
confidence: 99%
See 1 more Smart Citation